Caring for babies from 0 to 3 years of age in the community - Marcella Oliveira Araujo; Ana Paula Soares da Silva (Universidade Federal de Santa Catarina, 2017)
http://dx.doi.org/10.5007/1980-4512.2017v19n35p29 Based on an approach that considers the relational and situated constitution of the subjects in development, this article aims to present a picture about the care of infants from 0 to 3 years in community. This study was obtained from a master's research about the daily life of a group of children and families in the context of settlement of the agrarian reform. The organization of the times and environments of each child, by the people of their relational universe, revealed a community practice of care, in which their needs and wants are inserted as part of the collective activities of each family. Immersed in these networks of community relationships, we find that the way of life in the countryside is permeated by a strong network of solidarity created among the members of different generations of the family, to care for babies.